Management of two placenta percreta cases - Celik, Ebru; Kavak, Salih Burcin; Yavuzkir, Seyda; Pala, Sehmus; Kaplan, Selcuk; Sapmaz, Ekrem (Walter de Gruyter Gmbh, 2016)
Placental invasion anomalies are divided into three according to invasion of uterine wall as placenta accreta, increta and percreta. In placenta percreta, the most severe but the least common form, the placenta invades the full thickness of the uterine wall and also it can attach to adjacent organs in the abdomen like the bladder and rectum. It is a potentially life treating condition. There is no recommended management strategy for placenta percreta. We herein report two cases managed differently and discuss the management options in the light of the literature.
Keywords: Conservative management; hemorrhage; placenta percreta